Pemberdayaan Kelompok Belajar Komunitas Anak Pelangi (K-APEL) Melalui Ilmu dan Pengajaran dalam Pembelajaran Berdiferensiasi di Kota Makassar: Penelitian - Rahmi; Husni Bt Salam; Sirnan (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
The partner in this Community Service Program is the Komunita Anak Pelangi (K-Apel). The objectives of this community service program are to (a) improve the quality of learning facilities for the community's children; (b) provide age-appropriate teaching materials, learning media, and educational props; (c) provide training and mentoring to volunteers in developing creative and enjoyable teaching methods; (d) establish a simple documentation system to monitor children's learning progress; and (e) develop a more structured and sustainable learning activity structure. The methods used in this program include outreach, training, technology implementation, mentoring, evaluation, and program sustainability. The Community Service Program at the K-APEL Alley Campus was successfully implemented and had a positive impact on the community. This program was able to provide real solutions to the limited access to education for children in the alley through a creative, participatory, and simple technology-based approach.